PENGARUH RETURN ON ASSET (ROA) DAN INFLASI TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BEI PERIODE 2018-2022 - Febrianti; Muhammad Ilham Wardhana Haeruddin; Anwar; Muh. Ichwan Musa; Hety Budiyanti (MANAJEMEN DEWANTARA, 2024)
The purpose of this study was to determine the effect of return on assets and inflation on stock returns of telecommunications sector companies listed on the IDX for the period 2018 to 2022. The sampling technique in this study was purposive sampling where only 10 of the 16 populations were sampled. The research method used is descriptive method with a quantitative approach, with the classical assumption test data analysis method, multiple linear regression analysis and hypothesis testing. The results of this study partially show that the variable Return on Assets (ROA) has a negative and significant effect on stock returns, and the inflation variable has a negative and significant effect on stock returns. Simultaneously the variables Return on Assets (ROA) and Inflation have a significant effect on Stock Returns Telecommunication Sector Company 2018-2022 Period.